'(Dis)ordered intensification?' Techno-political models, resource access and pastoralist/agribusiness relations in the Middle Valley of the Senegal River. (1st March 2019) - Magnani, Sergio Dario; Ancey, Véronique; Hubert, Bernard
Abstract : Since the 1990s, the scientific literature has shown how the technical model of intensification of livestock production is ill adapted to the characteristics of semi-arid climates and the pastoral systems operating in them. While this led to changes in the rhetoric of pastoral development, there have been no significant shifts in its conceptual foundations and working methods. This article analyses the forms of this persistence, its effects and its causes in the Valley of the Senegal River through a study of the introduction of a social business dairy project into the pastoral area surrounding the city of Richard Toll. The industrial dairy producers and the pastoralists mutually use each other for their own ends, thereby reinforcing the discrepancy between their objectives and the logic of their systems. The model of intensification is persistent because it plays a political role in constructing alliances between actors from agribusiness, and because choices about land use and resource access are depoliticised and repeatedly made in their favour. The article underlines the urgency of re-politicising and rethinking the logic behind pastoral development and the challenges it faces, and of deconstructing the rhetoric of reconciling profit with social development which serves mainly to reinforce the role that private businesses play in shaping public action.